Il mulo di Lessing - Franco Perrelli (Drammaturgia, 2016)
In Hamburg Dramaturgy, the lengthy parallel analysis that Lessing devoted to the tragedies of Maffei and Voltaire about the figure of Merope, led him to an Enlightenment re-reading of Aristotle and to an hypothetical reconstruction of Euripides’ Cresphontes. In this way, the German critic was able to underline Euripides’ attitude to a technique of preliminary revelation of the characters and the nodal points of the plot: on one side, it can reduce the suspense; on the other, it avoids the most superficial coups de théâtre, shifting the tragic effect from ‘what’ to ‘how’ it occurs. Contesting the position of Abbé d’Aubignac and supporting Diderot, Lessing realized that a considerable part of this Euripidean technique is based on the remixing of diegesis and dramatic mimesis: it is an uncommon ‘hybrid’ of genres that appears efficacious and extremely useful (just like the intersection from which is generated a mule). Lessing’s analysis had an important and documented influence on the modern theatre: here, we can find a Sophoclean approach (Ibsen) and an Euripidean approach to the drama. In particular, the Euripidean line is developed in Strindberg’s epic dramaturgy and, in all its evidence, in Brecht.